2015
DOI: 10.1007/s00253-015-6405-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of mangrove sediment in Shenzhen Bay and gene cloning, characterization of an isolated phytase-producing strain of SPC09 B. cereus

Abstract: Phytases hydrolyze phytate to release inorganic phosphate, which decreases the requirement for phosphorus in fertilizers for crops and thus reduces environmental pollutants. This study analyzed microbial communities in rhizosphere sediment, collected in September 2012 from Shenzhen Bay, Guangdong, China, using high-throughput pyrosequencing; the results showed that the dominant taxonomic phyla were Chloroflexi, Firmicutes, and Proteobacteria, and the proportion of the beneficial bacteria, Bacillus, was 4.95 %.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In the present study, we focused on K. obovata and found that prokaryotic communities in mangrove roots were dominated by Proteobacteria, Chloroflexi, Bacteroidetes (previously Cytophaga–Flexibacter–Bacteroides), Planctomycetes, and Actinobacteria ( Supplementary Figure S1A ). The observation was consistent with previous reports (Andreote et al, 2012; Hong et al, 2015; Zhang et al, 2015). Among the Proteobacteria, Gamma-proteobacteria, Delta-proteobacteria, and Alpha-proteobacteria were the three most abundant classes in our sampling sites ( Supplementary Figure S1B ), in agreement with previous findings in Aegiceras corniculatum , Avicennia marina , and Sonneratia caseolaris (Yang et al, 2014; Alzubaidy et al, 2016; Chen et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we focused on K. obovata and found that prokaryotic communities in mangrove roots were dominated by Proteobacteria, Chloroflexi, Bacteroidetes (previously Cytophaga–Flexibacter–Bacteroides), Planctomycetes, and Actinobacteria ( Supplementary Figure S1A ). The observation was consistent with previous reports (Andreote et al, 2012; Hong et al, 2015; Zhang et al, 2015). Among the Proteobacteria, Gamma-proteobacteria, Delta-proteobacteria, and Alpha-proteobacteria were the three most abundant classes in our sampling sites ( Supplementary Figure S1B ), in agreement with previous findings in Aegiceras corniculatum , Avicennia marina , and Sonneratia caseolaris (Yang et al, 2014; Alzubaidy et al, 2016; Chen et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…Some PSB present higher P solubilizing ability than that of A. pittii gp-1, such as Pseudomonas trivialis BIHB 745 for Ca 3 (PO 4 ) 2 (827 mg/L) (Vyas and Gulati, 2009), Serratia marcescens RP8 for Ca 3 (PO 4 ) 2 (974 mg/L) (Misra et al, 2012), Acinetobacter sp. ASL12 for Ca 3 (PO 4 ) 2 (717 mg/L) (Liu et al, 2014), Bacillus cereus SPC09 for phytate (579.01 mg/L) (Zhang et al, 2015), Saccharomyces cerevisiae CICIMY008 for phytate (93 mg/L) (Chen et al, 2016), Burkholderia cepacia B116 for phytate (52.7 mg/L) (Oliveira et al, 2009). However, the multiple P sources utilizing ability promises gp-1 itself easily get used to environment, and therefore exhibits great potential for phosphate chemical industry and agro-ecosystems.…”
Section: Assessment Of Diversity and Phosphorus Solubilizing Capacitymentioning
confidence: 99%
“…Phosphorus solubilizing microbes especially PSB are widely distributed in soils, freshwater, seawater, and sediments (Liu et al, 2014(Liu et al, , 2017Zhang et al, 2015), and responsible for the cycling of insoluble P to soluble PO 4 3− ion. Numerous researches have concentrated on the screening of highly efficient PSB, and most PSB are Gram-negative bacteria and belong to Pseudomonas (Misra et al, 2012;Oteino et al, 2015), Acinetobacter (Liu et al, 2014(Liu et al, , 2015, Pantoea and Enterobacter (Park et al, 2011;Chen and Liu, 2019), and some PSB are Gram-positive bacteria belonging to Bacillus (Hanif et al, 2015;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, since pqqA, pqqB, pqqC, pqqD, and pqqE genes are conserved and arranged in that order in the pqq operon (pqqABCDE) (Shen et al, 2012), we selected the pqqB and pqqE genes to study the mPSB. Given the substantial wide distribution of PSB in natural ecosystems including soils, freshwater, seawater, and sediments (Zhang et al, 2015;Liang et al, 2020;Wan et al, 2020), we cannot completely rule out a possible contribution of phosphate solubilizing bacteria in the increase of P fractions in our compost treatments. The moderate but positive correlation of 16S bacteria with the labile-P supports the possibility of bacteria to intervene in the P solubilization in the composts.…”
Section: Relationships Between Compost's P Fractions and Microbiologimentioning
confidence: 99%